Reconstituting the Agora: Towards an Alternative Politics of Lifelong Learning - Ian Martin (Adult Education Research Conference, 2000)
The paper proposes an explicit politicisation of the idea of lifelong learning as learning for democracy – as distinct from the dominant but implicit account of it as learning to labour. This requires that adult education as an agent of lifelong learning reoccupies the political and curricular space in which citizens make democracy work.